2015
DOI: 10.1016/j.jphys.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women maintain body temperatures within safe limits during moderate-intensity aqua-aerobic classes conducted in pools heated up to 33 degrees Celsius: an observational study

Abstract: Healthy pregnant women maintain body temperatures within safe limits during moderate-intensity aqua-aerobic exercise conducted in pools heated up to 33 degrees Celsius. The study provides evidence to inform guidelines for safe water temperatures for aqua-aerobic exercise during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The highest mean core temperature for pregnant women with warm water (30°C) immersion cycling was 37.5°C (95% CI 37.3°C to 37.7°C38). Aqua-aerobic exercise in water temperatures ranging from 28.8°C to 33.4°C resulted in a mean core temperature of 36.7°C (95% CI 36.6°C to 36.8°C45). Studies assessing pregnant women during passive heating via sauna or a 40°C water immersion reported mean maternal core temperatures peaking at 37.6°C (95% CI 37.5°C to 37.7°C34) and 36.9°C (95% CI 36.8°C to 37.0°C41), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest mean core temperature for pregnant women with warm water (30°C) immersion cycling was 37.5°C (95% CI 37.3°C to 37.7°C38). Aqua-aerobic exercise in water temperatures ranging from 28.8°C to 33.4°C resulted in a mean core temperature of 36.7°C (95% CI 36.6°C to 36.8°C45). Studies assessing pregnant women during passive heating via sauna or a 40°C water immersion reported mean maternal core temperatures peaking at 37.6°C (95% CI 37.5°C to 37.7°C34) and 36.9°C (95% CI 36.8°C to 37.0°C41), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Using our modified Cochrane ROB V.2.0 tool, six studies (out of 12) had some concerns about (n=5) or were at high risk (n=1) of selection bias,39 detection bias45 and intervention bias 25 26 40 42…”
Section: Resultsmentioning
confidence: 99%
“…Recommendations in the prenatal literature as described by Brearley et al (2015) indicate ‘that the safe upper limit for maternal core temperature is 38.9 or 1.5 °C above resting core temperature,’ to prevent possible harm to the foetus (Brearley et al, 2015; Hartgill, Bergersen & Pirhonen, 2011; Lindqvist et al, 2003). During this study, the participants remained below this threshold in 99.7% of instances (883 instances) where body temperature was measured while the compression shorts were worn, with only two (0.3%) reports of single measurements of body temperature reaching 39.0 °C which were monitored as per normal practice in prenatal care with their maternity care provider.…”
Section: Discussionmentioning
confidence: 99%
“…A concern for the use of compression garments during pregnancy is the increase in skin temperature and apprehension that it will raise core body temperature. According to 2016 guidelines from the Royal Australian and New Zealand College of Obstetricians and Gynaecologists Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG) (2016) a rise in core temperature of less than 1.5 °C is widely accepted as safe during pregnancy and these and other experts routinely advise pregnant women to avoid overheating to prevent possible harm to the foetus (Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG), 2016; Brearley et al, 2015; Lindqvist et al, 2003). Previous empirical evidence suggested male and female athletes, aged 19–33, that the thermoregulatory response to wearing compression garments at recreational and high levels of training and competition did result in increased skin temperatures (Doan et al, 2003); however, the associated increases in core temperature were not great enough to have detrimental effects in ambient and temperate environments with relative humidity between 46% and 64% (Houghton, Dawson & Maloney, 2009; MacRae et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…6 Many forms of exercise modalities are presented in intervention studies with a wide variety of designs and variations. Although most studies are based on land exercises, some studies have used a "swimming" intervention, 16,17 "aquatic activities" or "water aerobics," [18][19][20][21][22][23][24] and an "immersion" exercise session. [25][26][27] Kamioka et al 28 reviewed the effects of aquatic exercise and concluded that there is insufficient evidence to report benefits for aquatic exercise due to poor methodological and reporting quality and heterogeneity of nonrandomized clinical trials.…”
mentioning
confidence: 99%